2015
DOI: 10.3892/etm.2015.2360
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of paeoniflorin on H2O2-induced apoptosis in PC12 cells by modulation of reactive oxygen species and the inflammatory response

Abstract: Abstract. Paeoniflorin (PF) is a product derived fromPaeoniae Radix and is commonly prescribed in traditional Chinese medicine. PF has been reported to exhibit neuroprotective, anti-ischemic, antioxidant, anti-inflammatory and anticancer effects. The neuroprotective properties of PF have been demonstrated in animal models of various neuropathologies. The present study investigated the effects of PF on hydrogen peroxide (H 2 O 2 )-induced apoptosis in PC12 cells, to improve the understanding of the mechanisms u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 28 publications
(36 reference statements)
1
18
0
Order By: Relevance
“…PAE was also able to inhibit the activation of the neuro-inflammatory factor NF-κB thereby alleviating H 2 O 2 -induced oxidative stress [26]. In the present study, we found that PAE, the most abundant component in XBJ injection [22], significantly inhibited the plasma sTREM-1 level in rats of endotoxin-induced sepsis.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…PAE was also able to inhibit the activation of the neuro-inflammatory factor NF-κB thereby alleviating H 2 O 2 -induced oxidative stress [26]. In the present study, we found that PAE, the most abundant component in XBJ injection [22], significantly inhibited the plasma sTREM-1 level in rats of endotoxin-induced sepsis.…”
Section: Discussionsupporting
confidence: 58%
“…In a transgenic mouse model of Alzheimer's disease, PAE attenuated amyloidogenesis and the inflammatory responses [25]. Its neuroprotective effect was also reported in rat cells, where PAE reduced H 2 O 2 -induced toxicity by blocking the activation of the neuro-inflammatory factor NF-κB [26]. Moreover in rats, PAE ameliorated ANIT-induced cholestasis by activating Nrf2 through an PI3K/Akt-dependent pathway [27], and improved regional cerebral blood flow and suppressed inflammatory factors in the hippocampus of rats with vascular dementia [28].…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism is very likely to be implicated in the effect of KST, since KST ameliorated ISO-induced behavioral deficits when the administration was started from week 0, but not from week 2 after starting ISO. Moreover, chemical constituents of YKS and KST have been reported to have neuroprotective effects [3336], suggesting that these compounds protect central cholinergic systems from ISO-induced dysfunction. This hypothesis is currently under investigation in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Paeoniflorin, a major pharmacological pinane monoterpene glucoside, was first isolated from the Ranunculaceae plant in 1963. It is widely accepted that paeoniflorin has antioxidant, anti-inflammation, hepatoprotective and neuroprotective effects (4)(5)(6)(7). In an adjuvant-induced arthritis model, paeoniflorin inhibited the expression of IL-1β, IL-6, IL-17, and TNF-α and upregulated the production of TGF-β1 (8).…”
Section: Introductionmentioning
confidence: 99%